2019
DOI: 10.1186/s12903-019-0919-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of toothpaste on oral health-related quality of life in people with dentine hypersensitivity

Abstract: BackgroundDentine hypersensitivity can impact functional status and everyday activities such as eating and talking. This study aimed to assess changes in oral health-related quality of life measures in individuals with dentine hypersensitivity following long-term use (24 weeks) of a commercially available toothpaste marketed for dentine hypersensitivity relief.MethodsThis study was conducted across two sites and enrolled 75 adults with ≥2 non-adjacent sensitive teeth. Participants were assigned to twice-daily … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…A long‐term study on the impact of DH and oral health‐related QoL demonstrated that using a dentifrice containing 0.454% w/w stannous fluoride required 8 weeks to show a reduction of the impact of DH on health‐related QoL 48 . Our study found that using CSPS and arginine dentifrices reduced the RS intensity caused by cold food and toothbrushing within 2–4 weeks.…”
Section: Discussionmentioning
confidence: 48%
“…A long‐term study on the impact of DH and oral health‐related QoL demonstrated that using a dentifrice containing 0.454% w/w stannous fluoride required 8 weeks to show a reduction of the impact of DH on health‐related QoL 48 . Our study found that using CSPS and arginine dentifrices reduced the RS intensity caused by cold food and toothbrushing within 2–4 weeks.…”
Section: Discussionmentioning
confidence: 48%
“…The effectiveness of dentine tubule occlusion depends on the size and shape of the constituent calcium phosphate particles. Spherical particles smaller than or comparable to the dentine tubule (approximately 1-2 µm) can infiltrate the tubules without disturbing other parts of the teeth 25,26) . When the size and morphology of the calcium phosphate nanoparticles embedded in the gel were studied using TEM, the size of the embedded nanoparticles was found to decrease from approximately 400 nm to 300 nm compared with the emulsion without gelatine.…”
Section: Discussionmentioning
confidence: 99%
“…The oral hygiene level was evaluated through the Turesky modification of the Quigley-Hein Plaque Index (TQHPI) ( Mason et al, 2019 ). All vestibular and oral surfaces of the teeth were stained with a plaque staining solution (CURAPROX PCA 260).…”
Section: Methodsmentioning
confidence: 99%
“…Albeit that DH is a chronic condition that can worsen over time and requires qualified treatment ( Zeola et al, 2019 ), patients often adapt to the inconveniences and do not seek medical help from dentists ( Mason et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%